(untitled) (World Bulletin of Public Health, 2025)
Chronic cerebral ischemia (CCI) is a progressive condition caused by insufficient blood supply to the brain, which leads to neurotrophic impairment, cognitive impairment, and an increased risk of dementia. An important role in the modern approach to the diagnosis and treatment of CCI is played by the analysis of microRNAs, which are involved in the regulation of inflammatory processes and neurotrophic responses.